1949
DOI: 10.1084/jem.89.6.687
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Cardiac Lesions, Closely Resembling Those of Rheumatic Fever, in Rabbits Following Repeated Skin Infections With Group a Streptococci

Abstract: Cardiac lesions, closely resembling those found in rheumatic fever, have developed in rabbits that sickened following multiple, successive skin infections with several serological types of group A streptococci.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

1950
1950
1978
1978

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(17 citation statements)
references
References 8 publications
1
15
0
1
Order By: Relevance
“…Since childhood he had experienced repeated attacks of asthma and many episodes of urticaria. Allergy is probably an important causative factor in rheumatic cardiovascular disease (16,(23)(24)(25)(26)(27) and in the cardiovascular disease of disseminated lupus erythematosus (30,(57)(58)(59)(60)(61)(62)(63)(64)(65). Furthermore, it has long been known that rheumatic injury to coronary arteries occurs and in some cases leads to sclerosis of these vessels (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19); and clinico-pathologic observations indicate that injury to coronary arteries caused by disseminated lupus erythematosus also occurs and can lead to sclerosis of these arteries (66,67).…”
Section: Discussionmentioning
confidence: 99%
“…Since childhood he had experienced repeated attacks of asthma and many episodes of urticaria. Allergy is probably an important causative factor in rheumatic cardiovascular disease (16,(23)(24)(25)(26)(27) and in the cardiovascular disease of disseminated lupus erythematosus (30,(57)(58)(59)(60)(61)(62)(63)(64)(65). Furthermore, it has long been known that rheumatic injury to coronary arteries occurs and in some cases leads to sclerosis of these vessels (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19); and clinico-pathologic observations indicate that injury to coronary arteries caused by disseminated lupus erythematosus also occurs and can lead to sclerosis of these arteries (66,67).…”
Section: Discussionmentioning
confidence: 99%
“…The remaining portion of streptococcal cells was resuspended in 0.05 M phosphate buffer, pH 6.1, containing 4% NaCl and 0.005 M EDTA with activated phage-associated lysin (13). The preparation of streptococcal protoplasts and isolation of the streptococcal membranes from this mixture was as previously described (21 solutions, these sera were prepared as follows: 500 ml of frozen fetal calf serum was thawed, heat inactivated for 30 min at 560C, distributed in 20-ml aliquots, and refrozen at -20°C until use.…”
Section: Methodsmentioning
confidence: 99%
“…In studies on experimental models of rheumatic fever in animals, a number of investigators (13,14) have emphasized the need for repeated closely spaced streptococcal inoculations with a marked cutaneous reactivity to streptococcal materials as being a prime prerequisite in inducing the pathological lesions which simulated rheumatic lesions found in man. Rantz and others (15)(16)(17)(18) have also suggested that, in man, repeated streptococcal infections are important for the disease process, and they cite the rarity of rheumatic fever before 3-4 yr of age as evidence for the necessity of an acquired hypersensitivity to streptococcal materials before rheumatic fever occurs.…”
Section: The Journal Of Clinical Investigation Volume 54 August 1974*mentioning
confidence: 99%
“…Particular attention was directed at acute and serial studies of lymphocyte cell surface markers in this disorder. For some time it has been held as an established clinical principle that acute rheumatic fever is somehow related to the host immune response to the streptococcus (1)(2)(3)(4)(5)(6)(7). Whether this response is principally mediated by humoral immunity and thus the products of bone marrow-derived lymphocytes (Bcells)1 (8,9) or whether cell-mediated mechanisms operating through thymus-derived lymphocytes (T-cells) (10)(11)(12) constitute the most significant aspect of the rheumatic inflammatory response still remains to be determined.…”
Section: Introductionmentioning
confidence: 99%